Capacity Building and Sustainability Efforts Water Resources - Muchamad Idam Choliq; Esti Wulandari; Laksono Djoko Nugroho (International Journal of Mechanical, Electrical and Civil Engineering, 2025)
Increasing the capacity and sustainability of water resources are major challenges in reservoir management, especially in areas that are highly dependent on water resources for domestic, agricultural, and industrial needs. The Sier Reservoir, which plays a vital role in providing water to the surrounding area, has experienced a decline in capacity due to sedimentation, uncontrolled flow, and changes in rainfall patterns due to climate change This study aims to identify optimization efforts that can increase the capacity of the sier reservoir and ensure the sustainability of its water resource management. The methodology used in this study includes literature studies, field observations, surveys, interviews with relevant stakeholders, and quantitative data analysis. The results of the study indicate that technical measures such as sedimentation cleaning, infrastructure improvements, and the implementation of technology-based monitoring systems can increase reservoir capacity.